Pemetaan dan Perancangan Perbaikan Proses Produksi untuk Persiapan Industri 4.0 di PT. X - Kevin Purnomo (Jurnal Titra, 2019)
PT. X is a manufacturing company produces circuit breaker products. PT. X needs to prepare the development based on the industri 4.0 era. The purpose of this research is mapping and evaluate each department to find out activities that have not and have applied the principle of industrial system 4.0, and make preparations improvements based on framework industry 4.0. The results of mapping and evaluation indicate there are five departments classified